An exploration of pediatric nurses' compliance with a medication checking and administration protocol - Gill, Fenella; Corkish, V.; Robertson, J.; Samson, J.; Simmons, B.; Stewart, D. (Jannetti Publications, Inc., 2012)
Purpose: This study examined nurses’ reported compliance with the medication administration protocol and explored reasons for noncompliance. Design and Method: A mixed-methods design incorporated a questionnaire (n = 72) and focus groups (n = 24). Results: Differences were found between the level of experience and protocol compliance. Noncompliance was widespread in the checking of identification bands and double-checking medications. Key factors influencing compliance were ward culture, type of drug, familiarity with patient and drug, and workload. The reported realities of practice were found to influence compliance with the medication administration protocol. Practice Implications: The discrepancies between protocol and practice in this setting underscore the need to more widely investigate compliance with medication administration protocols in other settings.